Tribalismo pós-moderno: Da identidade às identificações - Michel Maffesoli (Ciências Sociais Unisinos)
The article discusses the characteristics involved in what is presently called post-modern. Michel Maffesoli reaffirms the idea that tribalism will be the dominating value in the coming decades. Thus, he elegantly elaborates on the two roots contained in post-modern tribalism: on the one hand, by stressing aspects of tribalism that are simultaneously archaic and youthful and, on the other hand, by pointing out to its communal dimension along with the saturation of the concept of individual and the logic of identity